Structural and Volumetric Changes in the Aging Face - Gerth, David J. (Facial Plastic Surgery, 2015)
Traditional views on facial aging and associated therapies focused on soft tissue descent and skin texture changes. Recently, revolumization for age-related lipoatrophy has become increasingly popular. Researchers are now reporting objective studies examining processes of structural and volumetric changes with age in increasing frequency as well. To better understand and treat facial aging, the surgeon should review all available data. Presented here are current evidence-based studies regarding age-related changes in the facial skeleton and soft tissue envelope. By reviewing these changes by each anatomic subsite, the surgeon will be better equipped to develop an appropriate treatment plan, individualized for each patient.
Keywords: aging face; lipoatrophy; fat transfer; facial skeleton; facial rejuvenation